Effect of Pruning Intensities and Different Levels of Fertilizers on Jatropha Curcas L. under Irrigated Condition - Parmar, M. R.; Jadeja, D. B.; Tandel, M. B.; Patel, N. K.; Bardhan, Kirti; Prajapati, V. M. (Indian Forester, 2014)
The world continues to seek economically and environmentally sound alternatives to fossil fuel-based transportation of fuels and power. Energy crop Jatropha curcus L provide an attractive combination of high yield density, high net energy balances, low input requirements and has potential to be tailored for specific production and refining processes. Present study was conducted to evaluate the effect of pruning and fertilizer on growth and yield of Jatropha curcas L. There were three pruning intensities viz., P (No pruning), P (45 cm) and P (60 cm) and four levels of fertilizer 0 1 2 -1 -1 -1 viz., F (No fertilizer), F (60:60:60 g NPK plant ), F (80:80:80 g NPK plant ) and F (100:100:100 g NPK plant ). A clear 0 1 2 3 decreasing trend was observed from F to F in almost parameters under study. Interaction effect between intensities of 3 0 pruning and levels of fertilizer was found non significant in all growth parameters of Jatropha curcus L. From this study -1 the significant yield increased by P (60 cm) pruning and F (100:100:100 g NPK plant ) level of fertilizer gave best result 2 3 for getting higher yield and vegetative growth of Jatropha curcas L.